The Application of Waste Mussel Shell and Nitrogen - Phosphorus - Potassium (NPK) Fertilizer on The Growth Components of Jasmine (Jasminum) - Abdullah, Noorul Hudai; Sulaiman, Ahmad Aizat Putra; Jamil, Siti Zulaikha; Jupri, Muhammad Arifafifi; Mohammad Azmi, Mohamad Azim; Tuan Azman1, Tuan Muhammad Fikri Haziq; Hamid, Nor Baizura; Suwandi, Amir Khan; Ahmad, Noraziah; Abdul Salim, Nur Atikah; Mat Lazim, Zainab; Nuid, Maria; et al. (Multidisciplinary Applied Research and Innovation, 2020)
Chemical fertilizers have helped farmers in increasing crop production for ages but it also causes negative effects. The excessive nutrients caused by chemical runoff from the excess fertilizer reduces the amount of oxygen in the water as well as can contribute to the release of greenhouse gases such as carbon dioxide into the atmosphere. Besides that, chemical fertilizer can lead to soil acidification because of the decrease amount of organic matter in the soil. This study investigates the efficiency of the growth performance of the Jasmine (Jasminum) plant by using organic fertilizer from waste mussel shell powder and Nitrogen- Phosphorus- Potassium (NPK) on the Jasmine plant. The experiments were conducted to evaluate the effectiveness of waste mussel shells powder and NPK in aiding the growth of the jasmine plant. The fertilizer applied on jasmine plants with various concentrations which are 5g, 10g, 15g, 20g for waste mussel shell powder, and NPK. A major operating condition such as the height of the plant, the diameter of the stem, and soil pH are commonly physical measurements to measure plant growth. The data obtained from the growth performance of Jasmine plants after a few weeks, the concentration of 20g is the best fertilizer in growth performance. The effects of pH on soil were determined for waste mussel shell plant-soil to maintain in neutral pH, however; NPK fertilizer soil slightly reduces to acidic scale. The application of experimentally verified the application of natural fertilizer will provide good benefits to humans and the conservation of the environment.